H. A. HUBAREVA : PARENTESIS IN THE POETIC LANGUAGE OF YURII ANDRUKHOVYCH - HUBAREVA, H. A. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. Parenthesis is a special insertion, a phrase having been dropped among other things, it expresses such additional messages or passing associative remarks that complement, clarify, develop the main content of a statement. Syntactically, parenthesis is related to the phenomenon of insertion. Inserted constructions are a potentially unlimited means of realizing the speaker’s descriptive intentions due to the fact that the possibility of going beyond the linear organization of speech is represented in these structures. This potential of parenthesis is stipulated by its grammatical and intonational detachment from the basic sentence, unpredictability at the time of speech – real or feigned. The real unpredictability of an insertion creates an objective modality, complementing the content of the new information, important for its understanding from the point of view of a speaker feigned one generates subjective modality, because it expresses axiological intentions of a speaker, his / her emotional reactions to said. In poetic discourse, parenthesis is an important factor in shaping the content and intonation of a text, generates expressiveness. In the organization of a poetic text, the inserted components appear as a kind of destructive element, creating epicism, slowing down the rhythm. The appearance of the constructions inserted in it is due to the specifics of the narrative: parenthesis becomes an element of a lyrical monologue, in which it is predetermined by the author. Purpose. The purpose of the research is to reveal the structural-semantic and functional features of parentheses in the poetic language of Yurii Andrukhovych. Results. Yu. Andrukhovych quite often resorts to using inserted components that are equal to a word, phrase, sentence and even a complex syntactic whole. However, their connection with the structure of the basic sentence may be more or less close. In a closer connection, the parenthetical components are quasi-insertions, or parembol, which the author tends to use. Such insertions could exist as elements of a syntactic structure of a basic sentence, but, marked in brackets, they accentuate the conceptual and semantic information of a poetic text: they acquire value, become an intertextual unit, provide a humorous tone, and so on. From the point of view of semantic connection a lot of parentheses in the analyzed texts are passing remarks containing different additional information. But, despite the fleetingness, they are quite accentuated and serve to complement, express images, conveying not so much an additional as a parallel message to the main, the content of which in brackets, forming a metatext layer of information, attracts more attention. Thus, in the poem «Stances» a parembol conveys the involuntaryness of memories, but at the same time the information presented in brackets emphasizes the most vivid images of the lyrical hero’s memory and implicitly expresses an emotional assessment of pity for the past. Another parenthesis in the mentioned poetry is a separate quatrain and conveys a fragment of memories with many details, like a cinematic frame, and it is on it that the author seeks to focus. In Yu. Andrukhovych’s poetry, figuratively significant parentheses of a concise structure are indicative, creating a concrete-sensual background for the unfolding of the text. Emotionally evaluative comments-insertions, designed as exclamatory sentences, create expression at the same time. Interrogative units inserted in poetic reflections convey the thoughts or doubts of the lyrical hero. Indicative are also the contexts in which the interrogative intonation gives the inserted component the semantics of choice, in particular in poetry-memoirs: «will you see the river (glade? allée?)». Parenthesis clearly fits into the axiological parameters of the text. Inserted evaluative judgments often create irony of varying degrees of sharpness, as in the poems from the series «Letters to Ukraine» (in addition, the genre of the letter itself motivates insertion). At the same time, the insertions actualize the precedent situations of the Soviet reality, which, in fact, become the basis for the creation of irony. We find the special meaningfulness of parenthesis in its ability to establish a conceptual connection between key images. Insertion becomes an organic continuation of verbal images in the main sentence. It is noteworthy that Yu. Andrukhovych introduces quite extensive parentheses into the poetic text, as, for example, in the poetry «Children’s Land», which is a kind of reflection on the travel notes of the 17th century traveller Pavel Aleppo about the meeting with the Cossack land (a quote from them is given as an epigraph to poetry). The author’s reflection on the fate of children, the number of who in the families of Cossacks at one time deeply impressed the foreign traveller, is designed as an inserted construction. In an additional text, which is generally an intertextual fragment, the poet expressed deep sympathy for the tragic fate of unfortunate children, doomed to suffering from birth. Originality. The article considers a phenomenon of parentheses as a leading method of text reproduction in the poetic language of Yurii Andrukhovych. It is traced to what extent the connection between the main and additional message, expressed by an inserted construction, influences the formation of the sentence content as a whole. The functional load of parentheses in poetry as carriers of author’s intentions is determined. It is observed that the author’s idiostyle is characterized, among other things, by the ironic use of parentheses in the role of emotionally evaluative comments, providing quasi-insertions with the semantics of choice (the author seems to suggest possible options for understanding, plays with the reader in meanings) as well as elements that establish an associative link between key images of poetry. Conclusion. Observations of the language of poetry in the collection of the selected works by Yu. Andrukhovych testify to the structural and functional diversity of the parentheses used, which is one of the features of the author’s idiostyle, as well as the wide artistic possibilities of insertions in poetic language in general. Expressing, supplementing, fragmenting poetic information, parentheses in a way expand the content of a text, create a polyphony of the sound of the narrator’s voice. Further study of the specifics of the functional load of parentheses in the structure of the poetic narrative seems promising.